2011
DOI: 10.1615/interjenercleanenv.2012005876
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Possibility of the Maisotsenko Cycle Application to Decrease Cold Water Temperature in Cooling Towers

Abstract: In any explanation of cooling tower operation, it is shown that the ambient wet bulb temperature is a physical limit for water cooling. The main advantage of the Maisotsenko cycle (Mcycle) is the possibility to have the cold water temperature lower than the ambient wet bulb temperature, without violation of any physical principle. The idea is based on the fact that the ambient wet bulb temperature depends not only on the absolute humidity value, but also on a current air temperature. On the contrary, the dew p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…That is why it is worth to apply MCT in hot climates. Finally, Sverdlin et al [9] analyzed the M-Cycle cooling tower using simulation program which was validated on the basis of real field data, obtained from existing cooling towers. They confirmed that cooling towers through the M-Cycle may significantly reduce the water temperature.…”
Section: Cooling Tower Through the M-cyclementioning
confidence: 99%
“…That is why it is worth to apply MCT in hot climates. Finally, Sverdlin et al [9] analyzed the M-Cycle cooling tower using simulation program which was validated on the basis of real field data, obtained from existing cooling towers. They confirmed that cooling towers through the M-Cycle may significantly reduce the water temperature.…”
Section: Cooling Tower Through the M-cyclementioning
confidence: 99%
“…Morosuk et al [22,23] investigated the exergetic analysis and the coefficient of performance (COP) of MCTs. Although their work proved that MCTs could reduce the water temperature below the inlet air's wet-bulb temperature, it was still a challenge to design MCTs with complicated fills and confirm the real possibility of MCTs in laboratory tests [24]. The EPRI (Electric Power Research Institute) [25] conducted a complicated feasibility demonstration in the laboratory and greatly promoted the technological development of MCTs; however, the advanced fills with cross-counter-flow arrangement proposed by the EPRI were very hard to apply in TWCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although Maisotsenko cycle is used in different applications such as gas turbine [20][21][22][23][24][25][26][27][28][29][30][31], cooling towers [32][33][34][35] and electronic cooling, [36&37] this paper only focuses on the employment of M-cycle on air conditioning systems. Mahmood et al [7] has presented the only review paper in any reputed journal on M-cycle systems in which the application of Maisotsenko cycle has been classified into 3 main parts (HVAC, cooling tower, gas turbine) and each part has been fundamentally discussed.…”
mentioning
confidence: 99%